Sierra Leone : Sixth Review Under the Arrangement Under the Extended Credit Facility, Request for Waiver for Nonobservance of a Performance Criterion, Request for a Three-Year Arrangement Under the Extended Credit Facility, and. (IMF Staff Country Reports; Country Report ;, 2010)
The government of Sierra Leone is requesting a successor three-year Extended Credit Facility (ECF) arrangement to support their program to raise economic growth by increasing investment in infrastructure and developing an accessible financial sector. Fiscal policy in 2010 focuses on improving revenue collection to support capital spending while containing pressures on current expenditures. The global economic downturn slowed economic activity in 2009, but achieving single digit inflation remains a challenge. Fiscal policy performance during 2009 was broadly satisfactory. Monetary policy was expansionary toward the end of 2009.